Co-Inhibition of the Immunoproteasome Subunits LMP2 and LMP7 Ameliorates Immune Thrombocytopenia - Du, Sheng-hong; Xiang, Yu-jiao; Liu, Lu; Nie, Mu; Hou, Yu; Wang, Ling; Li, Ban-ban; Xu, Miao; Teng, Qing-liang; Peng, Jun; Hou, Ming; Shi, Yan (Frontiers in Immunology, 2021)
The immunoproteasome, a special isoform of the 20S proteasome, is expressed when the cells receive an inflammatory signal. Immunoproteasome inhibition proved efficacy in the treatment of autoimmune diseases. However, the role of the immunoproteasome in the pathogenesis of immune thrombocytopenia (ITP) remains unknown. We found that the expression of the immunoproteasome catalytic subunit, large multifunctional protease 2 (LMP2), was significantly upregulated in peripheral blood mononuclear cells of active ITP patients compared to those of healthy controls. No significant differences in LMP7 expression were observed between patients and controls. ML604440, an specific LMP2 inhibitor, had no significant impact on the platelet count of ITP mice, while ONX-0914 (an inhibitor of both LMP2 and LMP7) increased the number of platelets. In vitro assays revealed that ONX-0914 decreased the expression of FcγRI in ITP mice and decreased that of FcγRIII in ITP patients, inhibited the activation of CD4+ T cells, and affected the differentiation of Th1 cells in patients with ITP. These results suggest that the inhibition of immunoproteasome is a potential therapeutic approach for ITP patients.